Serum 25-Hydroxyvitamin D and Adipose Tissue Vitamin D Receptor Gene Expression: Relationship With Obesity and Type 2 Diabetes - Clemente-Postigo, Mercedes; Muñoz-Garach, Araceli; Serrano, Marta; Garrido-Sánchez, Lourdes; Bernal-López, M. Rosa; Fernández-García, Diego; Moreno-Santos, Inmaculada; Garriga, Nuria; Castellano-Castillo, Daniel; Camargo, Antonio; Fernández-Real, Jose M.; Cardona, Fernando; et al. (The journal of clinical endocrinology and metabolism, 2015)
Context:The relationship between 25-hydroxyvitamin D [25(OH)D] and obesity and type 2 diabetes is not completely understood. Vitamin D receptor (VDR) expression in adipose tissue (AT) is related to obesity and might be regulated by 1,25-dihydroxyvitamin D3 [1,25(OH)2D3].Objective:To analyze serum 25(OH)D and VDR gene expression in AT according to body mass index (BMI) and glycemic status and the effect of 1,25(OH)2D3 on AT according to BMI.Design and Patients:Two cohorts were studied: 1) 118 subjects classified according to their BMI (lean, overweight, obese, or morbidly obese [MO]) and their glycemic status (normoglycemic [NG] and prediabetic and diabetic [P&D]); and 2) 30 obese subjects (BMI > 30 kg/m2) classified as NG and P&D. VDR gene expression was analyzed during preadipocyte differentiation and in vitro stimulation with 1,25(OH)2D3 of AT explants from donors with different BMI values.Setting:University Hospital.Main Outcome Measures:Serum 25(OH)D, parathyroid hormone (PTH), and AT VDR gene expression.Results:25(OH)D levels were lower in P&D than NG subjects, significantly so in the lean and MO groups (P < .05). 25(OH)D levels correlated negatively with homeostasis model of assessment for insulin resistance (HOMA-IR) (r = −0.200; P = .032) and glucose (r = −0.295; P = .001), but not with BMI. VDR gene expression was higher in MO than in the other BMI groups (P < .05). 1,25(OH)2D3 increased VDR gene expression in AT from obese patients (P < .05) but not from lean subjects.Conclusions:25(OH)D levels are diminished in P&D compared to NG subjects, independently of BMI, and are closely related to glucose metabolism variables, suggesting that vitamin D deficiency is associated more with carbohydrate metabolism than with obesity. Moreover, AT has a different response to 1,25(OH)2D3 depending on the degree of obesity.